Health institutional dynamics in the management of malaria and bilharzia in Zimbabwe in the advent of climate change: A case study of Gwanda district - A Mbereko; M.J Chimbari; P Furu; S Mukaratirwa (Cogent Social Sciences)
Climate change impacts on the transmission and epidemics of vector-borne diseases (VBDs), hence an understanding of the institutional determinants that influence the response of national health systems is important. This study explored how institutional determinants influence health outcomes of malaria and bilharzia using the case study of Gwanda district, Zimbabwe, in the advent of climate change. Qualitative data were collected using in-depth interviews from representatives of public and private institutions; and organisations involved in the prevention and control of malaria and bilharzia. Results from the study showed that the Ministry of Health and Child Care of Zimbabwe and other relevant government ministries and departments involved in environmental and social issues, constituted the primary network in the control and prevention of malaria and bilharzia. Non-governmental organisations (NGOs) formed the secondary network that mainly mobilized resources or complimented the primary networks in the delivery of services. It was noted that there was an institutional structure primarily responsible for responding to malaria and bilharzia but it was not adequately prepared to address climate change-induced VBDs changes. Based on our findings, a framework for reducing vulnerability and enhancing resilience among populations affected by VBDs in the context of climate change was developed.